2011
DOI: 10.1108/01425451211183264
|View full text |Cite
|
Sign up to set email alerts
|

Decent work and work life quality in Nepal: an observation

Abstract: PurposeThis paper aims to review the situation of decent work (DW) and quality of work life (QWL) in the context of Nepal.Design/methodology/approachThe paper is based on a literature survey. Institutional arrangements for DW and QWL are studied in connection with current labor legislations, national policy documents, and company policies and initiatives. The status of DW and QWL is described, examining national policy documents published by the Government of Nepal, National Planning Commission, labor legislat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
(21 reference statements)
0
22
0
Order By: Relevance
“…has stated that employee engagement and working conditions is the most affecting factors in quality of work life and the quality of work life is better and less stressful in non-financial sector than financial sectors. Likewise, Adhikari, Hirasawa, Takakubo and Pandey (2011) has identified that there is no equal employment opportunity for men and women, lack of governance, wage discrimination between male and female, low capacity utilization of organization and increased dissatisfaction among employees at work, poor labor policy. So, these finding shows that in the context of Nepal the quality of work life in corporate sector has not satisfied because of the poor implementation of corporate governance in an organization which creates the problem of inequality, stressed and unsatisfied.…”
Section: Introductionmentioning
confidence: 99%
“…has stated that employee engagement and working conditions is the most affecting factors in quality of work life and the quality of work life is better and less stressful in non-financial sector than financial sectors. Likewise, Adhikari, Hirasawa, Takakubo and Pandey (2011) has identified that there is no equal employment opportunity for men and women, lack of governance, wage discrimination between male and female, low capacity utilization of organization and increased dissatisfaction among employees at work, poor labor policy. So, these finding shows that in the context of Nepal the quality of work life in corporate sector has not satisfied because of the poor implementation of corporate governance in an organization which creates the problem of inequality, stressed and unsatisfied.…”
Section: Introductionmentioning
confidence: 99%
“…The concept was driven by the gap between the real conditions faced by workers and the conditions expected to occur in the workplace, as an improvement of the quality of life (ILO, 2001). At first, the concept of decent work was regarded as an opportunity for women and men to get decent and productive work in an environment that upholds freedom, equality, security, and human dignity (Adhikari et al, 2011). Decent work is then interpreted as work that provide adequate opportunities and remuneration for work, social security, incorporates fundamental rights of workers relate to freedom of association, non-discrimination in work, and the absence of forced labour and child labour in abusive conditions (ILO, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the concept of decent work addresses broader issues compared to the quality of work-life. The definition of decent work covers both formal and informal sectors, while the quality of work-life focuses on the quality of service in the internal sector (Adhikari et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations